- Tanggung Jawab Afganistan Berdasarkan Hukum Humaniter Internasional Dalam Melindungi Anak-anak Korban Konflik Bersenjata: - - Yolanda Kartika Aditya; Jun Justinar (Faculty of Law, Universitas Trisakti, 2024)
Since World War II children have been forcibly engaged as prisoners of war and child soldiers. The armed conflict in Afghanistan is a non-international armed conflict between Taliban insurgent forces and the Afghan Government within the Afghan state. The violations that occurred were torture and murder of children, suicide attacks using improvised devices, attacks using landmines, and sexual violence against children. Children as civilians are protected under the 1949 Geneva Convention IV. The formulation of the problem is how Afghanistan's responsibility for the protection of children in the armed conflict in Afghanistan according to international humanitarian law. This research is a normative juridical research, utilizing secondary data sources, conducting qualitative analysis by drawing conclusions by inductive reasoning. The results show that Afghanistan's responsibility for the protection of children is to cooperate with several international organizations to provide donations for a decent life to these children, and provide full protection when children are made prisoners of war. The conclusion of the Afghan government's responsibility for the conflict is to protect civil society and provide compensation to the victims.